2015
DOI: 10.1016/j.pmrj.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience With Continuous Intrathecal Baclofen Trials Prior to Pump Implantation

Abstract: Continuous trials via an external catheter could be an option if patients and clinicians desire a comprehensive assessment of systemic and functional effects of ITB before pump implantation. The majority of AEs were minor and resolved spontaneously, and the most effective starting intrathecal dose was determined by pump insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The next step for these patients remained dose adjustments following the implantation of the pump. Overall, continuous intrathecal administration of the baclofen to evaluate its systemic and functional effects could be considered as a helpful method as mentioned by some authors 16 , but we believe it would put extra burden, both on the patient and the hospital by hospitalizing and using another trial pump for several days. After coming to a consensus on the implantation of the baclofen pump, all the patients were operated and a catheter was placed in the intrathecal space either via percutaneous route or via partial hemi-laminectomy in the right decubitus position usually at the 2-3 or 3-4 interlaminar spaces.…”
Section: Discussionmentioning
confidence: 98%
“…The next step for these patients remained dose adjustments following the implantation of the pump. Overall, continuous intrathecal administration of the baclofen to evaluate its systemic and functional effects could be considered as a helpful method as mentioned by some authors 16 , but we believe it would put extra burden, both on the patient and the hospital by hospitalizing and using another trial pump for several days. After coming to a consensus on the implantation of the baclofen pump, all the patients were operated and a catheter was placed in the intrathecal space either via percutaneous route or via partial hemi-laminectomy in the right decubitus position usually at the 2-3 or 3-4 interlaminar spaces.…”
Section: Discussionmentioning
confidence: 98%
“…One patient would have been missed with a single‐shot trial, as she required a higher baclofen dose to obtain efficacy. More recently, Phillips et al reported on 57 patients with refractory spasticity that underwent a continuous ITB trial . Spasticity significantly decreased during trial, with 34% of ambulatory patients progressing to a less restrictive assistive device by trial's end.…”
Section: Methodsmentioning
confidence: 99%
“…Although intrathecal dosing can be titrated, many patients need to “feel” the decreased hypertonicity. And, occasionally, some patients decline implantation as a result of not liking being “too loose” [7]. Adversely effecting lower extremity function in these circumstances is unacceptable.…”
Section: Case Scenariomentioning
confidence: 99%
“…Although ITB trialing is considered a relatively safe procedure, it is not completely risk‐free undertaking. The rate of complications during ITB trialing has been reported to be as high as 30%‐40% [7,8]. Adverse events may include nausea and vomiting, dizziness, paresthesia, drowsiness and sedation, spinal headaches, hypotonia, dizziness, paresthesia, hypotension, respiratory depression, infection, nausea/vomiting, urinary retention, hypotension, seizures, drowsiness/sedation, and coma.…”
Section: Case Scenariomentioning
confidence: 99%